Pengendalian Mutu Penyimpanan pada Industri Metal Substrate PT. XYZ dengan Metode FIFO - Ngudi Wiyatno, Tri; Afrilian, Dino (Green Publisher Indonesia, 2025)
Metal substrate is a medium that serves as a container for active catalyst materials. Catalysts in terms of exhaust gases are used to convert harmful pollutants in vehicle exhaust emissions, such as Carbon Monoxide (CO), Hydrocarbons (HC), and Nitrogen Oxides (Nox) into non-hazardous substances such as Carbon Dioxide (CO2), Water (H2O), and Nitrogen (N2). In the face of global market share, the metal substrate industry faces significant challenges to meet the demand of domestic and international markets with always available stock and timely delivery. This study aims to analyze and optimize the quality control system and stock management at PT. XYZ. This journal conducted a study that the application of quality management standards, stock management standards, and delivery standards to ensure that products produced and received by customers are things that need to be considered as an effort to avoid market claims. The importance of implementing a standardized quality management system, improving quality inspections, optimizing technology-based inventory management, utilizing automation and digitalization, empowering employees, and focusing on customer satisfaction are among the company's strategies in meeting market demand and strengthening its competitive position in the dynamic global market era. In addition, continuous improvement and fixing system weaknesses are very supportive to achieve customer satisfaction. Researchers found that the FIFO method can be used as an alternative in stock management and storage without worrying about deterioration in the quality of the resulting product, given that the materials used are almost entirely metal.